1985
DOI: 10.1111/j.1468-2958.1985.tb00074.x
|View full text |Cite
|
Sign up to set email alerts
|

The "Competent Communicator" as a Cognitive Prototype

Abstract: Past theories concerned with communicative competence have assumed that perceiver's evaluations of the competence of a communicative performance are based on a conception of the "ideal communicator. " Psychological theoty on categorization implies that this assumption is most viable if conceptions of 'prototypes" relevant to competence in general ("the communicatively competent person") are rich in defining characteristics relative to their logical superordinate ("the skilled person"), yet distinct from other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 20 publications
(30 reference statements)
2
13
0
Order By: Relevance
“…While several approaches to the measurement of the content of cognitive prototypes have been developed over the years [including reaction time measures when items are presented on a computer screen (e.g., Lord et al, 1984, study 1), content analysis of freely generated lists of descriptive adjectives (e.g., Pavitt & Haight, 1985), and evaluation of statements regarding the perceived similarity of photographs (e.g., Yarmey & Johnson, 1982)], cognitive prototype is most commonly operationally defined in terms of people's judgments about how well various attributes fit with categories (Lord et al, 1984;Rosch, 1978;Rosch & Mervis, 1975). Thus, questionnaire measures are frequently employed in the measurement of prototypicality, with the extent to which an item is endorsed on a carefully-constructed Likert scale being interpreted as the extent to which that item fits the prototype of the respondent.…”
Section: Organizationally-shared Cognitive Prototypes Of Effective Lementioning
confidence: 99%
“…While several approaches to the measurement of the content of cognitive prototypes have been developed over the years [including reaction time measures when items are presented on a computer screen (e.g., Lord et al, 1984, study 1), content analysis of freely generated lists of descriptive adjectives (e.g., Pavitt & Haight, 1985), and evaluation of statements regarding the perceived similarity of photographs (e.g., Yarmey & Johnson, 1982)], cognitive prototype is most commonly operationally defined in terms of people's judgments about how well various attributes fit with categories (Lord et al, 1984;Rosch, 1978;Rosch & Mervis, 1975). Thus, questionnaire measures are frequently employed in the measurement of prototypicality, with the extent to which an item is endorsed on a carefully-constructed Likert scale being interpreted as the extent to which that item fits the prototype of the respondent.…”
Section: Organizationally-shared Cognitive Prototypes Of Effective Lementioning
confidence: 99%
“…Might peers who are more engaged with the student's educational experience be more correspondent (Waldron & Yungbluth, 2007)? The cognitive schematic configuring of what constitutes competence may remain relatively stable over time (Canary & MacGregor, 2008;Pavitt, 1989Pavitt, , 1990Pavitt & Haight, 1985), yet the association of these concepts may be relatively fluid in the transition to the first semester of university experience. Are the cohort developmental effects of the college, and especially the freshman, experience in general, separable from the influences of exposure to the communication course specifically?…”
Section: Discussionmentioning
confidence: 98%
“…By implication, this work would contribute to mapping the repertoire of behaviors from which an actor would draw in order to communicate competently with a given person in a given situation. Pavitt and Haight (1985) suggest, however, that the behavioral repertoire map may be impossible to develop. These authors showed that elicited characteristics of competence would differ more across contextfree conceptions of specific skills than across context-specific conceptions under any one skill.…”
Section: Behavioral Repertoire Mappingmentioning
confidence: 90%